Pengaruh Brand Image, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Mobil Suzuki Ertiga Tipe Gl Wilayah Jakarta - Silviana Dora Afifah (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Purchasing decisions are an important thing to research because they relate to the sustainability of a company. The aim of the research is to determine the factors associated with increasing purchasing decisions in the automotive industry. The method used is multiple linear regression analysis to determine brand image factors, product quality and price quality factors in the automotive industry. Data collection was carried out using a questionnaire using an instrument composed of indicators for each variable. The research results show that there is an influence between brand image, product quality and price on purchasing decisions partially or simultaneously. The implications of the research show that consumers pay attention to brand image factors, product quality and price of the automotive products they want to buy. Thus, companies should pay attention to indicators assessed by consumers in increasing sales of their products